Eradication of Drug-Tolerant Mycobacterium tuberculosis 2022: Where We Stand - Alessio Lanni; Angelo Iacobino; Lanfranco Fattorini; Federico Giannoni (Microorganisms, 2023)
The lungs of tuberculosis (TB) patients contain a spectrum of granulomatous lesions, ranging from solid and well-vascularized cellular granulomas to avascular caseous granulomas. In solid granulomas, current therapy kills actively replicating (AR) intracellular bacilli, while in low-vascularized caseous granulomas the low-oxygen tension stimulates aerobic and microaerophilic AR bacilli to transit into non-replicating (NR), drug-tolerant and extracellular stages. These stages, which do not have genetic mutations and are often referred to as persisters, are difficult to eradicate due to low drug penetration inside the caseum and mycobacterial cell walls. The sputum of TB patients also contains viable bacilli called differentially detectable (DD) cells that, unlike persisters, grow in liquid, but not in solid media. This review provides a comprehensive update on drug combinations killing in vitro AR and drug-tolerant bacilli (persisters and DD cells), and sterilizing Mycobacterium tuberculosis-infected BALB/c and caseum-forming C3HeB/FeJ mice. These observations have been important for testing new drug combinations in noninferiority clinical trials, in order to shorten the duration of current regimens against TB. In 2022, the World Health Organization, following the results of one of these trials, supported the use of a 4-month regimen for the treatment of drug-susceptible TB as a possible alternative to the current 6-month regimen.